THE EFFECT OF OCCUPATIONAL HEALTH AND SAFETY HAZARDS ON EMPLOYEES’ PERFORMANCE: CASES FROM OMAN - KHALFAN AL AZRI, DR. ABDULLAH; RAMACHANDRAN, DR. NITHYA; AL-MATANI, BUSHRA KHALFAN; AL-RAWAHI, HANIN YASSER (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Occupational Health and Safety (OHS) is a critical component in enhancing employee performance, particularly in high-risk sectors such as manufacturing. This study investigates the impact of OHS hazards specifically health, safety, and ergonomic hazards on employee performance in selected manufacturing companies in the Sultanate of Oman. Grounded in a conceptual framework linking these OHS dimensions as independent variables and employee performance as the dependent variable, the research employs a quantitative approach using a structured survey administered to 335 employees across five manufacturing firms. Reliability was tested using Cronbach’s Alpha, with values exceeding 0.78 for all constructs. Data were analyzed through Confirmatory Factor Analysis (CFA), regression analysis, and Structural Equation Modeling (SEM) using SPSS and SmartPLS. The findings indicate that all three OHS hazards significantly affect employee performance, with ergonomic hazards exhibiting the strongest influence. The results underscore the necessity of proactive OHS strategies, employee training (such as the Train-the-Trainer model), and adherence to international standards like ISO 45001 to mitigate risks and enhance workplace productivity. Additionally, the study reveals that organizations in Oman are increasingly aware of the positive correlation between OHS practices and performance outcomes. Recommendations include continuous safety education, professional certification, and the development of specialized teams to monitor and improve OHS compliance. This research contributes to literature on OHS in the GCC context, particularly Oman, and offers practical insights for policy formulation and organizational practice. Future research could explore sectoral differences and incorporate longitudinal designs for deeper analysis.